Nie wszystko „tarło” co ma zęby – w poszukiwaniu funkcji - Waszczuk, Kamilla; Żychliński, Daniel; Pachulski, Piotr; Prawniczak, Robert (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2016)
This article presents the research related to identifying the actual function of an object made of deer bones excavated in Kujawy, in the village of Brzezie (site 4). It was discovered in the remains of a partly dug building, most probably residential, dated back to the 12th – 13th centuries. Originally, the historic object in question was identified as an ancient percussion instrument. However, in the course of microscopic tests and experiments this interpretation was rejected. It was stated that the artefact could not have served to clean animals’ skins, either. Finally, in the course of research procedures, it was agreed that it was a tool for decorating clay vessels.